Pengaruh Sistem Informasi Pengelolaan Keuangan Daerah Dan Penerapan Anggaran Berbasis Kinerja Terhadap Kinerja Pemerintah Daerah - Yuliani, Nur Laila (Universitas Muhammadiyah Yogyakarta, 2014)
This research aimed to examine the influance of local financial management information system and implementation of performance-based budgeting toward performance of local government and public accountability. The mainspring of this research is motivated by empirical studies on the performance of local government and public accountability are still diverse and growing importance of local government performance assessment and public accountability as a form of accountability to the central government and the society. The research sample consisted of 104 SKPD employees in Magelang regency. This research provides evidence that the area of local financial management information system has an influence on the performance of local government but has no effect on public accountability, while the implementation of performance-based budgeting has a good effect on the performance of local government and public accountability. Moreover the good performance of local government can increase the value of public accountability.